ANALISIS PREFERENSI SISWA MEMILIH SMA BOARDING SCHOOL BABUSSALAM PEKANBARU TAHUN AJARAN 2014/2015 - Yusmarni '; Raja Arlizon Raja Arlizon; Tri Umari Tri Umari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. Preference Analysis of High School Students Choosing a Boarding School Babussalam Pekanbaru (Hj. Yusmarni, Amd). Formulation of the problem in this research are: 1. Is the internal aspects are becoming preference Boarding School high school students choose Babussalam Pekanbaru. 2. Is the external aspects into preference Boarding School high school students choose Babussalam Pekanbaru. 3. How does the internal preference category Boarding School high school students choose Babussalam Pekanbaru. 4. How is the external preference category Boarding School High School students choose Babussalam Pekanbaru. To find a picture of Preference High School Students Choosing a Boarding School Babussalam Pekanbaru, the authors felt a tingle take action against this research. As for the other penelitianara manfaatukan: 1. For a tutor and counseling, the counselor can help prepare the programs in order to overcome the problems of students in select schools. 2. For students, it can be used as information for students to choose the right school. 3. For parents, can direct the child in selecting and continuing to high school Boarding School Babussalam Pekanbaru. 4. For schools, can be used as guidelines for menungkatkan quality of educational services provided. 5. For researchers, broaden horizons and contribute to researchers. The sample in this study were all students of class X High School Boarding School Babussalam Pekanbaru academic year 2014/2015 as many as 102 students. This research method using a quantitative approach, which aims to explain or describe the aspects that influence the selection of high school Boarding School Babussalam Pekanbaru. The tools used in this study was a questionnaire (questionnaire) with a total number of 28 items questionnaire statement. In accordance with the issues raised then to examine and determine the level of accuracy problems in this study used a descriptive statistical analysis techniques, namely data analysis is an activity that is very important and requires research and criticality of researchers. From these results it can be concluded that in general internal preference Boarding School high school students choose Babussalam Pekanbaru because you want to explore the religion of Islam, and only a small percentage of students who choose the internal preference for wanting to become a cleric / cleric and want to continue to study the state of Al-Jazair. And external preference Boarding School high school students choose Babussalam Pekanbaru for wanting the proud parents, and only a small proportion of external preference of students for solicitation of friends. Keywords: Analysis, Preferences, Students Choosing, Boarding School